Transformasi Kepemimpinan Kiai dalam Lembaga Pendidikan Pesantren - Robiatul Adawiyah; Muhammad Husni (CV. Lentera Literasi Indonesia, 2026)
Islamic boarding schools (pesantren) play a significant role in shaping the character, morality, and intellectual development of Muslims in Indonesia. The sustainability and development of pesantren are closely linked to the leadership of the kiai, who serves as a central figure with religious, spiritual, and social authority. In the era of globalization, rapid technological advancement, and increasing demands for educational quality, pesantren are required to undertake various reforms in their management and educational practices. This study aims to analyze the characteristics of kiai leadership, examine the forms of leadership transformation within pesantren educational institutions, and explore their implications for improving the quality of Islamic education. The study employs a qualitative approach using a library research method by reviewing relevant books, scholarly journals, and previous research findings. The results indicate that the transformation of kiai leadership is characterized by a shift from charismatic leadership to a more transformational, professional, participatory, and adaptive leadership model. This transformation is reflected in the modernization of pesantren management systems, the development of integrative curricula, the enhancement of human resource quality, and the utilization of digital technology in educational and administrative processes. Furthermore, the transformation of kiai leadership contributes positively to educational quality improvement, institutional governance strengthening, increased competitiveness of pesantren, and the preservation of traditional pesantren values. Therefore, the transformation of kiai leadership serves as a strategic factor in maintaining the sustainability and relevance of pesantren amid social change and technological advancement.